2022
DOI: 10.35459/tbp.2021.000206
|View full text |Cite
|
Sign up to set email alerts
|

Authentic Science Learning During COVID-19: The Adaptive Design of a SEM Outreach Activity

Abstract: Before March 2020, with the outbreak of the COVID-19 pandemic, remote instruction of science was only moderately developed compared with more traditional approaches for learning science. Since the outbreak, however, all formal education systems have been carried out in remote mode, and outreach activities that take place in a research or academic setting have usually been canceled, or there has been a search for innovative approaches to shift to digital space. Therefore, the development of learning and teachin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 38 publications
(46 reference statements)
0
10
0
Order By: Relevance
“…Only three lecturers mentioned the need for comprehensive knowledge about TPACK before the semester began, four lecturers indicated that they needed it at the end of the semester. Such knowledge included, for example, dedicated teaching applications in mathematics and technology, allowing students to perform lab experiments remotely [ 52 ]. The need for additional TPK increased after the lecturers had taught during the online semester (from 16% to 23%), since the lecturers had invested much effort to develop their TPK during the semester, much more than they had expected (from 41% to 58%).…”
Section: Resultsmentioning
confidence: 99%
“…Only three lecturers mentioned the need for comprehensive knowledge about TPACK before the semester began, four lecturers indicated that they needed it at the end of the semester. Such knowledge included, for example, dedicated teaching applications in mathematics and technology, allowing students to perform lab experiments remotely [ 52 ]. The need for additional TPK increased after the lecturers had taught during the online semester (from 16% to 23%), since the lecturers had invested much effort to develop their TPK during the semester, much more than they had expected (from 41% to 58%).…”
Section: Resultsmentioning
confidence: 99%
“…The learning environment of the SEM device was designed at the Weizmann Institute of Science, and it has been implemented since 2018 . It was initially set as a face-to-face (f2f) learning environment and was later adapted to a remote mode of a similar nature due to the constraints of the COVID-19 pandemic . The goals of the remote SEM activity, as presented to the students, were to Meet a scientist who applies the SEM in her/his research work Prepare a personal sample to be examined by the SEM Examine the sample with the SEM by remote control …”
Section: The Study: the Sem Remote Activity And Learning Environmentmentioning
confidence: 99%
“…Previous work with this device showed that a teachers' workshop with the SEM was successfully adapted from f2f to remote mode while preserving many authentic features of the SEM learning environment. 35 This included, for example, experiencing an actual research environment, operating a research device, and more. An additional study with teachers showed the SEM device as suitable for inquiry projects that engage learners' interest and are in the scope of secondary science education.…”
Section: ■ Introductionmentioning
confidence: 99%
See 2 more Smart Citations